“Breaking a vicious cycle”: the reproduction of ableism in higher education and its impact on students with disabilities - Goodall, Gemma; Mjøen, Odd Morten; Witsø, Aud Elisabeth; Horghagen, Sissel; Kvam, Lisbeth (Frontiers in Education, 2024)
IntroductionDespite the widespread promotion of inclusive learning environments, students with disabilities have to exert time and effort in gaining accommodations and proving themselves as competent individuals. In following up a factorial survey experiment that found that students with disabilities are considered less likely to achieve their educational goals compared to students without, this study explored how understandings of inclusive education and disability are constructed within Norwegian higher education institutions.MethodNineteen employees across 10 universities participated in focus group interviews. Transcripts were analyzed using thematic analysis.ResultsThree themes were generated: (1) determining the role of the educator, (2) knowing how, when, and why to grant accommodations, (3) calling for action from the university.DiscussionOverall, the findings suggest that understandings of inclusion are ambiguous and characterized by juxtaposing ideals. The participants’ accounts illustrate how they are tasked with promoting inclusion while simultaneously protecting their respective professions. Thus, despite being considered a resource based on their diversity, students with disabilities are still expected to fit into an environment designed for mainstream learners. In discussing these findings in light of ableist theory, we argue that more action is needed on a systemic level to restructure how inclusive education is understood and practiced.